Disjoint difference families with block size 3 - Dinitz J.H.; Rodney P. (Utilitas Mathematica, 1997)
A disjoint (v,k,λ) difference family is a difference family with disjoint blocks. We show that disjoint (v,3,1) difference families exist for all v ≡ 1 mod 6.